"Hard" ceramics for "Soft" tissue engineering: Paradox or opportunity?. (1st October 2020) - Kargozar, Saeid; Singh, Rajendra K.; Kim, Hae-Won; Baino, Francesco
Abstract: Tissue engineering provides great possibilities to manage tissue damages and injuries in modern medicine. The involvement of hard biocompatible materials in tissue engineering-based therapies for the healing of soft tissue defects has impressively increased over the last few years: in this regard, different types of bioceramics were developed, examined and applied either alone or in combination with polymers to produce composites. Bioactive glasses, carbon nanostructures, and hydroxyapatite nanoparticles are among the most widely-proposed hard materials for treating a broad range of soft tissue damages, from acute and chronic skin wounds to complex injuries of nervous and cardiopulmonary systems. Although being originally developed for use in contact with bone, these substances were also shown to offer excellent key features for repair and regeneration of wounds and "delicate" structures of the body, including improved cell proliferation and differentiation, enhanced angiogenesis, and antibacterial/anti-inflammatory activities. Furthermore, when embedded in a soft matrix, these hard materials can improve the mechanical properties of the implant. They could be applied in various forms and formulations such as fine powders, granules, and micro- or nanofibers. There are some pre-clinical trials in which bioceramics are being utilized for skin wounds; however, some crucial questions should still be addressed before the extensive and safe use of bioceramics in soft tissue healing. For example, defining optimal formulations, dosages, and administration routes remain to be fixed and summarized as standard guidelines in the clinic. This review paper aims at providing a comprehensive picture of the use and potential of bioceramics in treatment, reconstruction, and preservation of soft tissues (skin, cardiovascular and pulmonary systems, peripheral nervous system, gastrointestinal tract, skeletal muscles, and ophthalmic tissues) and critically discusses their pros and cons (e.g., the risk of calcification and ectopic bone formation as well as the local and systemic toxicity) in this regard. Statement of Significance: Soft tissues form a big part of the human body and play vital roles in maintaining both structure and function of various organs; however, optimal repair and regeneration of injured soft tissues (e.g., skin, peripheral nerve) still remain a grand challenge in biomedicine. Although polymers were extensively applied to restore the lost or injured soft tissues, the use of bioceramics has the potential to provides new opportunities which are still partially unexplored or at the very beginning. This reviews summarizes the state of the art of bioceramics in this field, highlighting the latest evolutions and the new horizons that can be opened by their use in the context of soft tissue engineering. Existing results and future challenges are discussed in order to provide an up-to-date contribution that is useful to both experienced scientists and early-stage researchers of the biomaterials community. Graphical abstract: Image, graphical abstract